Ukraine vs. Darkness : Undiplomatic Thoughts - Shcherba, O. V. (Oleksandr Vasylʹovych); Karatnycky, Adrian (Stuttgart : Ibidem Verlag, 2021)
"This book draws on the author's experience from 26 years of Ukrainian diplomatic service in, among others, Bonn, Berlin, Washington, and Vienna, and his work as a speechwriter to most Ukrainian foreign ministers for the last two decades. Scherba's captivating essays reflect his views of international affairs from a Ukrainian perspective. His deliberations are presented in uncomplicated, plain language. The articles assembled here have repeatedly caused discussion in Ukraine and abroad. By his opponents, Scherba is often described as being surprisingly undiplomatic and even provocative. For instance, his article "Why nationalism can't be the national idea of a European Ukraine", published on a Ukrainian nationalist website, stirred considerable controversy in Ukraine. Aside from explaining Kyiv's take on some key issues of international relations, these essays provide insights into Ukrainian political thinking since the start of Russia's military aggression in 2014, and into the painful political intramural fights in Ukrainian society ever since"--
Foreword / Adrian Karatnycky -- "We will never be slaves!" -- The three goodbyes -- For whom the bell tolls -- Reconfiguring Europe's mental map -- Euromaidan. Flashback -- Pandora's Box of evils -- Crimea, Donbas and the USSR 2.0 -- Ukraine-Russia. What went wrong -- From dusk till dawn -- Going against the flow -- Battle for Europe. Battle for the soul -- Why nationalism can't be the idea of a European Ukraine -- Ukraine, the Church and the post-truth world -- The Strasbourg betrayal -- Surkov and emptiness -- Notes on the margin of (yet another) apocalypse -- What will bring peace to Ukraine's soul?
Online resource; title from PDF title page (Ebsco, viewed February 27, 2025).
eBooks on EBSCOhost
Keywords: Ukraine -- Politics and government -- 1991-2014.; Ukraine -- Politique et gouvernement -- 1991-2014.; Politics and government; Ukraine; Since 1991